An Evaluation on The Applicability of Block Chain Technology in Disaster and Risk Management - Gür Türkdoğan, Tuğçe (Atlas Journal, 2024)
It is stated that in the current social formation, large-scale disasters are increasing rapidly, and their effects are spreading throughout the global system. In this context, societies need to be able to identify existing risks and take innovative and coercive measures to mitigate threats on a global scale (Comfort and Rhodes, 2022: 1). The transboundary nature of the crisis requires urgent corrective action with deep uncertainty, and in this process, the new level of information technology has the capacity to respond to the search for innovative solutions in the management of disaster and risk situations. Blockchain technology is expressed as a new level reached by the digitalization process and draws attention with its applicability in the disaster and risk management process through its technical features. Blockchain, a distributed ledger technology, consists of a series of protocols based on cryptography, simultaneously accessible, decentralized, shared, data recording, storing, verifying, and updating. In this context, this new generation technology has a significant potential in solving administrative problems that arise before, during and after disasters. Areas such as identity management, smart contracts and supply chain and social aid networks are expressed as prominent areas in terms of the applicability of blockchain technology in disaster management.